Whole-Genome Sequence of Burkholderia ambifaria Strain Q53, a Potential Plant Growth Promoter Isolated from the Rhizosphere of Peanut - Nievas, Fiorela Lujan (2023)
We report the complete genome sequence of Burkholderia ambifaria strain Q53, an environmental rhizobacterium isolated from the rhizosphere of peanut plants. The genome consists of 7.4 Mbp distributed into three circular chromosomes and was determined using a hybrid long- and short-read assembly approach.